Comparative Study to Evaluate the Antimicrobial Effect of MTAD, 17% EDTA, and 3% NaOCl- Against Enterococcus faecalis in Primary Teeth for Root Canals Therapy (in Vitro Study). (Medico Legal Update, 2020)
Aim: This study presented to compare the antimicrobial effect of MTAD, 17% EDTA, and 3% NaOCl, against Enterococcus faecalis (E. faecalis).Methodology: The study utilized 40 extracted human primary teeth with single root canal. The samples were instrumented and sterilized, and then, these teeth were infected with E. faecalis for 2 weeks, after that tooth were divided randomly into 2 groups according to the irrigants used. All the samples were incubated in brain heart infusion (BHI) broth. Irrigation processes were completed according to each material instruction. The effectiveness of irrigants was evaluated by comparison between the pre-irrigation and post- irrigation samples using serial dilution (CFU/ml).Statistical analysis was done using one-way anova with dunnett t3 post hoc test.Results: all samples treated with MTAD showed nearly complete absence of bacteria. the samples treated 3% NaOCl and 17% EDTA showed similar result to the first group, Statistical analysis of the data using dunnett t3 test showed there is no significant difference between the groups (P > 0.05).Conclusion: The study concluded that MTAD was effective as 3% NaOCl -17% EDTA against E. faecalis.